2004
DOI: 10.1128/iai.72.12.7096-7106.2004
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the Endogenous Salmonella enterica Serovar Typhi clyA -Encoded Hemolysin for Antigen Export Enhances the Immunogenicity of Anthrax Protective Antigen Domain 4 Expressed by the Attenuated Live-Vector Vaccine Strain CVD 908- htrA

Abstract: Bacterial live-vector vaccines aim to deliver foreign antigens to the immune system and induce protective immune responses, and surface-expressed or secreted antigens are generally more immunogenic than cytoplasmic constructs. We hypothesize that an optimum expression system will use an endogenous export system to avoid the need for large amounts of heterologous DNA encoding additional proteins. Here we describe the cryptic chromosomally encoded 34-kDa cytolysin A hemolysin of Salmonella enterica serovar Typhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
66
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 56 publications
0
66
0
1
Order By: Relevance
“…In a recent demonstration of the remarkable tunability of OMVs by our group, heterologous proteins fused with the native bacterial protein ClyA are efficiently transported in their native functional forms to vesicles (22). Previous work also points to the utility of ClyA in enhancing the immunogenicity of antigens secreted from a live attenuated Salmonella vector, further suggesting the possibility that antigens may be exported from live vectors in the form of OMVs (23).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a recent demonstration of the remarkable tunability of OMVs by our group, heterologous proteins fused with the native bacterial protein ClyA are efficiently transported in their native functional forms to vesicles (22). Previous work also points to the utility of ClyA in enhancing the immunogenicity of antigens secreted from a live attenuated Salmonella vector, further suggesting the possibility that antigens may be exported from live vectors in the form of OMVs (23).…”
Section: Discussionmentioning
confidence: 95%
“…1, depicting antibody titers in mice immunized with the purified proteins, show ClyA to be an effective carrier protein for enhancing the immunogenicity of GFP. The immunogenicity of ClyA fusion proteins was first shown in a study by Galen et al (23), where the observed enhancement in the immune response to the antigens was postulated to be largely dependent on export from a live Salmonella vector. Here, the results show that antigen fusion with ClyA is directly responsible for enhanced immunogenicity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These recombinant Salmonella vaccines can target mucosal inductive tissues (PP) and ultimately disseminate and stimulate both mucosal and systemic arms of the immune system (29,30). It has been shown that the attenuated strain S. Typhi can serve as a safe and effective oral vaccine to prevent typhoid fever and serve as a live vector to deliver heterologous Ags in humans (31)(32)(33)(34). To enhance the immunogenicity of passenger Ag expression by live Salmonella vaccines (35), various types of promoters have been tested to enhance passenger Ag expression.…”
Section: Discussionmentioning
confidence: 99%
“…There were trials to deliver the antigen using surface display and secretion of ClyA (9,10). In this work, 193-aa S1E epitope from SARSCoV S protein was chosen as a cargo antigen because this has been well characterized as a receptor binding domain (22) and vaccine candidate (14).…”
Section: Discussionmentioning
confidence: 99%